2015
DOI: 10.1007/s10980-015-0184-6
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of spatio-temporal landscape patterns for protected areas in northern New England: 1900–2010

Abstract: Context Landscape ecology theory provides insight about how large assemblages of protected areas (PAs) should be configured to protect biodiversity. We adapted these theories to evaluate whether the emergence of decentralized land protection in a largely private landscape followed the principles of reserve design. Objectives Our objectives were to determine: (1) Are there distinct clusters of PAs in time and space?(2) Are PAs becoming more spatially clustered through time? and (3) Does the resulting PA portfol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 36 publications
1
8
0
2
Order By: Relevance
“…and the estimated I = 0.44 for the pattern of architectural landscape in Jinan, China (Xue et al 2015). These urban landscapes represent a higher degree of fragmentation than the protected areas in northern New England (Meyer et al 2015), where the highest values of Moran's I > 0.70 are similar to the landscapes we simulated with the highest autoregression coefficient (φ = 0.999).…”
Section: Discussionsupporting
confidence: 60%
“…and the estimated I = 0.44 for the pattern of architectural landscape in Jinan, China (Xue et al 2015). These urban landscapes represent a higher degree of fragmentation than the protected areas in northern New England (Meyer et al 2015), where the highest values of Moran's I > 0.70 are similar to the landscapes we simulated with the highest autoregression coefficient (φ = 0.999).…”
Section: Discussionsupporting
confidence: 60%
“…Nevertheless, Canova () and Meyer et al . () showed that the process of habitat change (encompassing increasing urban areas, changes in farming and decreasing natural habitats) was substantially mitigated in PAs, and promoted higher species richness. Similarly, the greater stability of landscape dynamics is likely to explain the enhanced effect of PAs on specialist species.…”
Section: Discussionmentioning
confidence: 97%
“…Note, however, that this hypothesis should be confirmed by finer investigations of the relationships between habitat stability and PA, but relevant and high-resolution data on temporal land use changes are still lacking. Nevertheless, Canova (2006) and Meyer et al (2015) showed that the process of habitat change (encompassing increasing urban areas, changes in farming and decreasing natural habitats) was substantially mitigated in PAs, and promoted higher species richness. Similarly, the greater stability of landscape dynamics is likely to explain the enhanced effect of PAs on specialist species.…”
Section: Species Responses To Pas Facing Climate Changementioning
confidence: 99%
“…Revealing the patterns that impact the efficiency of PAs networks for biodiversity conservation, our results can inform management decisions and influence the prioritization of conservation efforts. This is especially important given that the future PAs networks will likely face fragmentation problems due to the increase in the proportion of smaller PAs (Maiorano et al, 2015; Meyer, Beard & Cronan, 2015) and urban expansion around PAs (Bonet-García et al, 2015; Martinuzzi et al, 2015; Wood et al, 2015). …”
Section: Resultsmentioning
confidence: 99%